APPLICATION OF RTV SILICONE RUBBER COATING FOR IMPROVING PERFORMANCE OF CERAMIC OUTDOOR INSULATOR UNDER POLLUTED CONDITION - PRATOMOSIWI (NIM: 23207005), FARI
This thesis reports the investigation results on application Room Temperature Vulcanize (RTV) Silicone Rubber for improving the performance of ceramic outdoor insulator 20 kV to overcome the effect of environmental pollution, especially in tropical climate. Both insulators, non-coated and RTV Silicon Rubber coated insulator tested under various environmental conditions (artificial tropical climate and pollution). The samples were put in a test chamber with controlled humidity and pollution condition. AC 50Hz voltage is applied from 10-60 kV .The characteristics of RTV Silicon Rubber coated insulator were analyzed, such as its leakage current (LC), contact angle which indicates the hidrophobicity of insulator surface and surface smoothness with Scanning Electron Microscopy (SEM) technique. From the experiment, it was found that leakage current magnitude and waveform depend on the insulator surface. In order to improve the diagnostic tool and to deeply understand the behaviour of the leakage current on the outdoor insulators we will also proposed an equivalent electrical circuit model for modelling leakage current phenomenon on ceramic outdoor insulator with RTV Silicone Rubber Coating under various environmental conditions. In general, the proposed equivalent electrical circuit model consists of capacitor(s), non-linear resistor(s), and arc model(s). These three parameters will be used to simulate the LC waveforms of ceramic insulator under various environmental conditions. Both experimental and simulation results indicated that RTV silicone rubber coated insulator can maintain its hydrophobicity suppressed the magnitude of leakage current, the harmonic content of leakage current and increased the flashover voltage under various artificially - simulated pollution. The low LC corresponds with high surface resistance which indicates high quality of insulator under various polluted condition. These results will be basis of application of RTV Silicon Rubber coated insulator under polluted conditions, especially in Indonesia.